Sharing Mobility und der öffentliche Raum. Herausforderungen der Mobilitätswende. - Stratil-Sauer, Gregor (Forum Landschaftsplanung - AbsolventInnenverband, 2020)
Car oriented city planning has come to an end and cities are searching for the future of urban mobility. The Smart City Framework Strategy for Vienna sets amitious targets for reducing car trips and car ownership. A lot of new sharing mobility services are being tested and new business models are rolled out very fast, sometimes without a clear strategy. The promise to reduce car dependency, but the claim urban space and generat new conflicts. Integration and regulation of these new services is an novel challenge for cities.
Keywords: Mobilitätsentwicklung; Nachhaltige Stadtentwicklung; Öffentlicher Raum; Freiraumgestaltung; Straßenraumgestaltung; Stadtplanung; Sharing Mobility; Mobilitätswende